2011
DOI: 10.1111/j.1467-8535.2010.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving teaching and learning of computer programming through the use of the Second Life virtual world

Abstract: The emergence of new technologies such as three-dimensional virtual worlds brings new opportunities for teaching and learning. We conducted an action research approach to the analysis of how teaching and learning of computer programming at the university level could be developed within the Second Life virtual world. Results support the notion that it is possible to use this environment for better effectiveness in the learning of programming. The main results are the identification of problems hampering the tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 38 publications
1
67
0
4
Order By: Relevance
“…Further examples of publications on virtual worlds in education are the many books and book chapters published (see e.g. Molka-Danielsen & Deutschmann, 2009;Peachey, Gillen, Livingstone, & Smith-Robbins, 2010a;Wankel & Kingsley, 2009). A related theme to possibilities is barriers (Conole & Alevizou, 2010;Esteves et al, 2011;Inman et al, 2010;Petrakou, 2010;Rapanotti et al, 2012;Wang & Burton, 2013). These two themes often appear in tandem in previous studies.…”
Section: Teaching In Virtual Worldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further examples of publications on virtual worlds in education are the many books and book chapters published (see e.g. Molka-Danielsen & Deutschmann, 2009;Peachey, Gillen, Livingstone, & Smith-Robbins, 2010a;Wankel & Kingsley, 2009). A related theme to possibilities is barriers (Conole & Alevizou, 2010;Esteves et al, 2011;Inman et al, 2010;Petrakou, 2010;Rapanotti et al, 2012;Wang & Burton, 2013). These two themes often appear in tandem in previous studies.…”
Section: Teaching In Virtual Worldsmentioning
confidence: 99%
“…A dominating theme of interest in previous literature concerns the possibilities virtual worlds have in an educational context (Annetta, Folta, & Klesath, 2010;Conole & Alevizou, 2010;Deutschmann, 2012;Esteves, Fonseca, Morgado, & Martins, 2011;Inman, Wright, & Hartman, 2010;Kim, Lee, & Thomas, 2012;Petrakou, 2010;Rapanotti, Minocha, Barroca, Kamel Boulos, & Morse, 2012;Wang & Burton, 2013). Several concepts are used in these studies when describing this interest, such as opportunities, affordances, potentials, facilitations and strengths.…”
Section: Teaching In Virtual Worldsmentioning
confidence: 99%
“…Other proposals make use of new technologies such as three-dimensional virtual worlds, for better effectiveness in the learning of programming [19].…”
Section: Networked Programmingmentioning
confidence: 99%
“…The pedagogical context in which students learn influences their engagement and resolve to achieve learning outcomes [12,13], and much research has examined approaches to the above described problem employing project-based learning (PBL) and teamwork environments [14,15,16]. While engineering problems are designed so that multiple solutions of varying mathematical and scientific sophistication are possible, teamwork skills and both oral and written communication skills used to model these problems are essential to the success of future engineers [8].…”
Section: Introductionmentioning
confidence: 99%
“…Literature addressing engineering education has reported that current learning approaches do not align with the professional practice required by the labor market [6,7]. These approaches are narrowly focused upon the acquisition of technical knowledge supported by heavy workloads and promote a meritocracy of difficulty-based belief system instead of prioritizing active learning and integrating knowledge, skills more aligned with professional realities [8,9,10,11].The pedagogical context in which students learn influences their engagement and resolve to achieve learning outcomes [12,13], and much research has examined approaches to the above described problem employing project-based learning (PBL) and teamwork environments [14,15,16]. While engineering problems are designed so that multiple solutions of varying mathematical and scientific sophistication are possible, teamwork skills and both oral and written communication skills used to model these problems are essential to the success of future engineers [8].…”
mentioning
confidence: 99%